Questions vs. Queries in Informational Search Tasks - White, Ryen W.; Richardson, Matthew; Yih, Scott Wen-tau (Proceedings of the companion publication of the 24th international conference on World Wide Web, 2015)
Search systems traditionally require searchers to formulate information needs as keywords rather than in a more natural form, such as questions. Recent studies have found that Web search engines are observing an increase in the fraction of queries phrased as natural language. As part of building better search engines, it is important to understand the nature and prevalence of these intentions, and the impact of this increase on search engine performance. In this work, we show that while 10.3% of queries issued to a search engine have direct question intent, only 3.2% of them are formulated as natural language questions. We investigate whether search engines perform better when search intent is stated as queries or questions, and we find that they perform equally well to both.